2017
DOI: 10.1038/srep44224
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific, Nonlinear Surface Ozone Damage to Rice Production in China

Abstract: China is one of the most heavily polluted nations and is also the largest agricultural producer. There are relatively few studies measuring the effects of pollution on crop yields in China, and most are based on experiments or simulation methods. We use observational data to study the impact of increased air pollution (surface ozone) on rice yields in Southeast China. We examine nonlinearities in the relationship between rice yields and ozone concentrations and find that an additional day with a maximum ozone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…We summarize the results of the two sets of regressions in table . We measure ozone pollution using AOT40, a cumulative metric, which is the sum of hourly ozone concentrations exceeding 40 ppb over the growing season; see Tong et al (2007), McGrath et al (2015), and Carter et al (2017), among others . We report results for unbalanced‐panel yield models with county‐specific linear trends and controlling for weather.…”
Section: The Effect Of Nox Emissions On Crop Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…We summarize the results of the two sets of regressions in table . We measure ozone pollution using AOT40, a cumulative metric, which is the sum of hourly ozone concentrations exceeding 40 ppb over the growing season; see Tong et al (2007), McGrath et al (2015), and Carter et al (2017), among others . We report results for unbalanced‐panel yield models with county‐specific linear trends and controlling for weather.…”
Section: The Effect Of Nox Emissions On Crop Yieldsmentioning
confidence: 99%
“…Recent papers that employ regression techniques to evaluate the effects of pollution on crop yields include Carter et al (2017), McGrath et al (2015), Burney and Ramanathan (2014), and Auffhammer, Ramanathan, and Vincent (2006). Carter et al study the effects of ozone on rice yields in China.…”
mentioning
confidence: 99%
“…Concerning human health, O 3 can cause injuries to airway epithelial cells (and lung diseases such as asthma), hyperplasia, headaches, and nausea, particularly in sensitive people, such as children and elderly [6][7][8][9][10]. Regarding vegetation, O 3 can damage plant leaves (decreases in both leaf photosynthesis and leaf area), reducing crop yields associated with a high negative economic impact [11][12][13]. Moreover, as a strong oxidant, it is responsible for the degradation of material via corrosion [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further estimates of decreased yields in important crops due to exposure to O3 have been reported. In a study of production of rice in China, 161 it was shown that, for each day with concentrations of O3 > 240 µg m -3 , there was a loss of yield of 1.12% ± 0.83%. The authors point out that increased concentrations of O3 at ground-level in China may lead to reductions in rice yields large enough to have implications for the global rice market.…”
Section: Adverse Effects Of Poor Air Quality On Vegetation Crop Planmentioning
confidence: 99%